Prospek Pengembangan Usahatani Jamur Merang (Volvariella volvacea) di Kecamatan Cilamaya Kulon Kabupaten Karawang - Chindy Diana Putri; Abubakar Abubakar; Luthfi Nur’azkiya (Jurnal Ilmiah Wahana Pendidikan, 2021)
The research objective was to determine the cost and revenue as well as how the prospect of mushroom farming development based on the benefits and feasibility of Cilamaya Kulon District, Karawang Regency. The research method used is descriptive analytic method. Primary data collection by interview technique using a questionnaire. Research respondents were producers or farmers of edible mushrooms, while secondary data were obtained from various literatures and documents from related agencies related to research. The samples were determined using a quota sampling technique taken from several sub-populations or strata. The analysis techniques used are NPV, IRR, NET B / C and Payback Period. The results showed that the total fixed costs incurred for cultivating edible mushrooms for 4 years was Rp. 15,482,486 and Rp. 97,521,263 for variable costs. Revenue obtained by farmers is Rp. 159,319,746. The results of the development prospect analysis based on the advantages and the feasibility show that the mushroom farming in the Cilamaya Kulon District is feasible to be continued and developed with an NPV value of Rp. 32,866,796 / 37 , IRR of 113%, Net B / C of 3.67 and Payback Period for 5 months and 4 days at the prevailing interest rate of 11.25% during the age of 4 years of mushroom farming.